(untitled) (Journal Of Educational and Psychological Researches, 2022)
The present research aims to design an electronic system based on cloud computing to develop electronic tasks for students of the University of Mosul. Achieving this goal required designing an electronic system that includes all theoretical information, applied procedures, instructions, orders for computer programs, and identifying its effectiveness in developing Electronic tasks for students of the University of Mosul. Accordingly, the researchers formulated three hypotheses related to the cognitive and performance aspects of the electronic tasks. To verify the research hypotheses, a sample of (91) students is intentionally chosen from the research community, represented by the students of the college of education for humanities and college of education for pure sciences. The researchers adopt the experimental design of one group. The sample has been taught through the electronic system according to study plans developed by the researcher. To measure the dependent variable, this requires formulating two instruments: the first is a test that measured the cognitive aspect of the electronic tasks that consisted of two questions, the first included (40) multiple-choices and the second is a matching and pairing type with ten items. The second instrument is a performance test for electronic tasks of (25) items that included (166) performance steps. The research experiment starts with the beginning of the first semester of the academic year (2020/2021). It began on Tuesday (5/1/2021) and lasts for (9) weeks approximately to be finished on Sunday (7/3/2021). The results revealed that there is a statistically significant difference at the level of significance (0.05) between the mean scores of the cognitive test for electronic tasks for the research sample in the pre and post applications in favor of the post-application. There is a statistically significant difference at the level of significance (0.05) between the mean scores of the performance test for electronic tasks for the research sample in the pre and post applications in favor of the post-application. Thus, the researcher came out with several recommendations and suggestions.